Performance evaluation of nitrogen gas-assisted laser cutting on 316L austenitic stainless steel plate - Abd. Halim, Shahrizal (2010)
Austenitic stainless steel in particular 316L has played an important role in the history of medicine for centuries. It is the most widely used material for medical devices, implants and controlled drug delivery systems. Stainless steels are popular class of engineered material because of its strength, corrosion resistance and oxidation resistance at temperatures up to 550oC. Austenitic stainless steels are typical difficult to machine by the traditional methods and also non-traditional method. Laser cutting which is very prominent amongst the non-conventional machining methods is expected to be used quite extensively in cutting austenitic stainless steel due to the favourable features and advantages that it can offer. This project was undertaken to evaluate the cutting performance of laser cutting on austenitic stainless steel. The effects of cutting parameters such as laser power, cutting speed and gas pressure on the machining responses such as kerf width (KeW), surface roughness (SR) and striation width (SW) were investigated. The experimental plans were conducted according to the design of experimental (DOE) and analysis of variance (ANOVA) was employed in evaluating the experimental data. Subsequently mathematical models for KeW, SR and SW were established. Results showed that laser power and cutting speed were significant in influencing the cutting responses during laser cutting of austenitic stainless steel 316L.